Characterization of clays deposits and their application/ Hazman Seli and Siti Hajar Anaziah Muhamad - Seli, Hazman; Muhamad, Siti Hajar Anaziah (2013)
The study will begin with the the collection of raw materials in Matang area with the help of Jabatan Mineral Dan Geosains Malaysia, Cawangan Sarawak. The experimentation will be conducted in lab facilities in the School of Materials Engineering USM. Raw materials collected will be cleaned and prepared in powder form and in fired body. Then the samples are chemically, physically and mechanically characterized in the laboratory to identify the important properties for ceramic industry applications. All data collected will be analyzed and discussed in a complete research report.